2019
DOI: 10.1155/2019/9184769
|View full text |Cite
|
Sign up to set email alerts
|

Hoveniae Semen Seu Fructus Ethanol Extract Exhibits Anti-Inflammatory Activity via MAPK, AP-1, and STAT Signaling Pathways in LPS-Stimulated RAW 264.7 and Mouse Peritoneal Macrophages

Abstract: Hoveniae semen seu fructus (HSF, fruit and seed of Hovenia dulcis Thunb) is an important traditional herbal medicine and food supplement in East Asia for the treatment of liver diseases, alcohol poisoning, obesity, allergy, and cancer. HSF has also been reported to have anti-inflammatory activity, but the cellular mechanism of action is not fully understood. We assessed the anti-inflammatory properties of an HSF ethanol (HSFE) extract and explored its precise mechanism. The ability of HSFE to suppress inflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 36 publications
2
30
0
Order By: Relevance
“…Macrophages exposed to LPS during microorganism infections stimulate the immune system to produce cytokines and chemokines, followed by inflammatory events. Thus, inhibiting macrophage activation by LPS is an important focus for therapeutic strategies aimed at treating inflammatory diseases [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Macrophages exposed to LPS during microorganism infections stimulate the immune system to produce cytokines and chemokines, followed by inflammatory events. Thus, inhibiting macrophage activation by LPS is an important focus for therapeutic strategies aimed at treating inflammatory diseases [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different studies reported above highlighted the anti-inflammatory activity of H. dulcis extracts explicated through the inhibition of pathway and mediators known to be crucial for the development of inflammatory reaction, such as NFKB, TNF-α, IL-1, IL-10, etc. [ 48 , 49 , 67 , 68 ]. The anti-inflammatory effect of H. dulcis fruits ethanol extract in a mouse macrophage RAW 276.7 cells model was investigated.…”
Section: Pharmacological Activities Of H Dulcis mentioning
confidence: 99%
“…Results showed that H. dulcis extract significantly inhibited, in a dose-dependent manner, the expression of NO, nitric oxide synthase, COX-2, interleukin-1b, TNF-α, the nuclear translocation of NF-kB, p65 and the phosphorylation of IkB in the cytoplasm [ 67 ]. A similar in vitro study conducted by Jeong et al [ 48 ] assessed the anti-inflammatory effect and the mechanism of action of Hoveniae semen seu fructus extracts in the murine macrophage cell line (RAW 264.7) and mouse primary macrophages. They demonstrated that H. dulcis ethanol extract (10, 30 and 50 mg/mL) strongly inhibited, in a concentration-dependent manner, the phosphorylation of MAPK and reduced the activation of activator protein-1 (AP-1), janus kinase-2 (JAK2)/STAT and NF-κB in LPS-stimulated RAW 264.7 cells.…”
Section: Pharmacological Activities Of H Dulcis mentioning
confidence: 99%
See 1 more Smart Citation
“…AP-1 is a mediator of M1 macrophage polarization [ 93 ]. That transcription factor is a target for Persicaria chinensis and Hovenia dulcis extracts in a study conducted on RAW264.7 cells [ 94 , 95 ]. AP-1 protein is also downregulated in LPS-activated RAW 264.7 macrophages by patriscabrin F, an iridoid obtained from Patrinia scabra [ 75 ], koreanaside A, a lignan isolated from the Forsythia koreana [ 76 ] and torilin, a sesquiterpene from Torilis japonica [ 96 ].…”
Section: Plants and Their Active Compounds As Modulators Of Macropmentioning
confidence: 99%